Retinal Sensitivity before and after Silicone Oil Removal Using Microperimetry - Ghada A. Nassar; Maha M. Youssef; Lameece M. Hassan; Hebatalla S. Makled (Journal of Ophthalmology)
The purpose of the study is to assess the retinal sensitivity, using microperimetry, before and after silicone removal. It included 22 patients admitted for silicone removal after vitrectomy for macula-off retinal detachment. Patients were divided into 2 groups according to the duration of silicone tamponade: Group A: <3 months (included 10 patients), and Group B: 3–6 months (included 12 patients). Retinal sensitivity was tested, using microperimetry, one day before and one month after silicone removal. The best-corrected visual acuity (in LogMAR) significantly improved postoperatively (0.69 versus 1.06 and 0.69 versus 1.07 in Groups A and B, respectively). The mean intraocular pressure (IOP) was 12.89 ± 1.05 mmHg postoperatively versus 14.89 ± 1.76 mmHg preoperatively in Group A (p=0.011) and was 13.33 ± 1.30 mmHg postoperatively versus 15.33 ± 3.11 mmHg preoperatively in Group B (p=0.008). In Group A, the mean postoperative overall retinal sensitivity was 8.70 ± 2.56 dB versus 5.68 ± 2.00 dB preoperatively (p=0.008). In Group B, it was 9.83 ± 3.36 dB versus 7.00 ± 2.55 dB (p=0.002). No statistically significant difference was found between the two groups as regards improvement in overall retinal sensitivity. We concluded that the overall retinal sensitivity significantly increased following silicone removal in both groups. This trial is registered with ISRCTN43187564.